Outside the box? Women's individual poverty risk in the EU and the role of labour market characteristics and tax-benefit policies - Katrin Gasior; Silvia Avram; Daria Popova (University of Essex, Institute for Social and Economic Research (ISER), 2024)
Social policy debates as early as the 1950s have focused on the activation of individuals into employment.. This assumes jobs with good working conditions and fair pay; ignores women's reality of part-time work, unpaid care work and the gender pay gap; and has often resulted in the weakening of traditional social protection. We study the individual poverty risk of women under the adult worker paradigm across the EU using the tax-benefit model EUROMOD and EU-SILC data. Comparing the individual poverty risk of working-age women to the benchmark of typical male workers, we highlight heterogeneity driven by women's economic situation and job characteristics and analyse the role of the tax-benefit system in reducing the gap. The analysis shows that only slightly more than one third of women fit the adult worker model, while this is the case for almost two thirds of men. Inactive and unemployed women are particularly likely to be vulnerable to poverty, but even women with the same characteristics as male reference workers experience a higher poverty risk, highlighting the role of the gender pay gap. Benefits cushion some of the gendered labour market dierences but are often not generous enough for unemployed and inactive women or not suciently available for self-employed women. Women in atypical employment are furthermore disproportionally aected by taxes and social insurance contributions as they lead to a higher poverty rate, contributing to a larger gap compared to typical male workers.
Keywords: 330; individual poverty risk; adult worker model; gender gap; employment